The impact of bookkeeping on the survival and growth of small and medium enterprises: a case of the Green Market complex in Mutare, Zimbabwe - Nyakatswau, Kudzanai (Midlands State University, 2017)
The research was on the impact of bookkeeping on the survival and growth of small and medium enterprises .The study was motivated by the fact that new players enter the field each year and almost the same number leave. A similar trend has been like that from 2010 to 2013 at the Mutare Green Market complex. An in-depth review of the literature related to the aforementioned factors under study was carried out. Qualitative and quantitative research methods were used in gathering information. Administering of five interviews and thirty three Questionnaires were the techniques employed to gather data. Major findings were that small businesses at the Green Market Complex in Mutare kept business records, the majority of them use single entry bookkeeping system and that this bookkeeping practice were not effective in improving their survival and growth. The study recommends that the government should make it mandatory for SMEs to submit yearly financial statements, impart accounting skills to the SMEs through seminars and that the SMEs owners should take the initiative to get workshops done for them and outsource the bookkeeping services.